Detection of some stable species during the oxidation of methane by coupling a jet-stirred reactor (JSR) to cw-CRDS - Bahrini, Chiheb (2012)
We present the coupling of a jet-stirred reactor to detection by cw-CRDS in the near infrared and first results obtained during the oxidation of methane. The mixture is rapidly expanded from the jet-stirred reactor into a 80 cm-long cw-CRDS cell maintained at a the pressure around 1.33 kPa, thus freezing the reaction and decreasing pressure broadening of the absorption lines. Some stable species (CH(4), H(2)O and CH(2)O) have been quantified through their well structured spectra around 1506 nm, while H(2)O(2) and HO(2) radicals could not be detected.